Yale Brain Atlas to interactively explore multimodal structural and functional neuroimaging data - Collins, Evan; Chishti, Omar; McGrath, Hari; Obaid, Sami; King, Alex; Qiu, Edwin; Gabriel, Ellie; Shen, Xilin; Arora, Jagriti; Papademetris, Xenophon; Constable, R. Todd; Spencer, Dennis D.; et al. (Frontiers in network physiology, 2025)
Understanding the relationship between structure and function in the human brain is essential for revealing how brain organization influences cognition, perception, emotion, and behavior. To this end, we introduce an interactive web tool and underlying database for Yale Brain Atlas, a high-resolution anatomical parcellation designed to facilitate precise localization and generalizable analyses of multimodal neuroimaging data. The tool supports parcel-level exploration of structural and functional data through dedicated interactive pages for each modality. For structural data, it incorporates white matter connectomes of 1,065 subjects and cortical thickness profiles of 200 subjects both from the Human Connectome Project. For functional data, it includes resting-state fMRI connectivity matrices for 34 healthy subjects and task-specific fMRI activation data acquired from two meta-analytic resources–Neurosynth and NeuroQuery–which, once translated into Yale Brain Atlas space and modified to include 334 function-specific terms, form Parcelsynth and ParcelQuery, respectively. Altogether, to support investigation of brain structure-function relationships, this study presents a web tool and database for the Yale Brain Atlas that enable scalable, interactive exploration of multimodal neuroimaging data.